Political consumerism: A comparative analysis of established and developing democracies - Gunderlach, Birte (International Political Science Review)
Research on political consumerism has focused predominantly on highly developed democracies. This focus has led to theoretical explanations closely connected to the social and political transformations of advanced industrialized democracies. In times of globalization and individualization, political consumerism is assumed to originate in political distrust stemming from perceived governance gaps. Recently, political consumerism has become a more frequent form of political participation in the Global South and a research topic attracting increased attention. The inclusion of the Global South requires a re-evaluation of political distrust as a general stimulus for political consumerism because of its conceptual links to socio-economic contexts in the Global North. This article provides such a re-evaluation and thereby advances the comparative analysis of political distrust as an important impetus of political consumerism in established as well as developing democracies.- Reproduced
Keywords: Political consumerism, Political trust, Developing countries, Globalization, Political participation